Design of Pd-Based Bimetallic Catalysts for ORR: A DFT Calculation Study - Lihui Ou (Journal of Chemistry)
Developing Pd-lean catalysts for oxygen reduction reaction (ORR) is the key for large-scale application of proton exchange membrane fuel cells (PEMFCs). In the present paper, we have proposed a multiple-descriptor strategy for designing efficient and durable ORR Pd-based alloy catalysts. We demonstrated that an ideal Pd-based bimetallic alloy catalyst for ORR should possess simultaneously negative alloy formation energy, negative surface segregation energy of Pd, and a lower oxygen binding ability than pure Pt. By performing detailed DFT calculations on the thermodynamics, surface chemistry and electronic properties of Pd-M alloys, Pd-V, Pd-Fe, Pd-Zn, Pd-Nb, and Pd-Ta, are identified theoretically to have stable Pd segregated surface and improved ORR activity. Factors affecting these properties are analyzed. The alloy formation energy of Pd with transition metals M can be mainly determined by their electron interaction. This may be the origin of the negative alloy formation energy for Pd-M alloys. The surface segregation energy of Pd is primarily determined by the surface energy and the atomic radius of M. The metals M which have smaller atomic radius and higher surface energy would tend to favor the surface segregation of Pd in corresponding Pd-M alloys.